2021
DOI: 10.1186/s13046-021-02107-1
|View full text |Cite
|
Sign up to set email alerts
|

MEST promotes lung cancer invasion and metastasis by interacting with VCP to activate NF-κB signaling

Abstract: Background Cell invasion is a hallmark of metastatic cancer, leading to unfavorable clinical outcomes. In this study, we established two highly invasive lung cancer cell models (A549-i8 and H1299-i8) and identified mesoderm-specific transcript (MEST) as a novel invasive regulator of lung cancer. We aim to characterize its biological function and clinical significance in lung cancer metastasis. Methods Transwell invasion assay was performed to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Among these genes, the partial control of human leucocyte antigen (HLA) genes like HLA-DQB2 on immune response to infection (45,46) could be used as a reasonable therapeutic target, which will be further explored to revive the antitumor immunity in ALL. Some studies have demonstrated that MEST promotes invasion and metastasis of solid tumors and by coordinating and activating the NF-κB and Wnt/β-catenin signaling pathways (47,48), which is consistent with our findings of MEST gene and its related signaling pathways in ALL. The functional and clinical significance of MEST and its potential target against ALL 10.3389/fped.2022.999684 could be considered.…”
Section: Discussionsupporting
confidence: 92%
“…Among these genes, the partial control of human leucocyte antigen (HLA) genes like HLA-DQB2 on immune response to infection (45,46) could be used as a reasonable therapeutic target, which will be further explored to revive the antitumor immunity in ALL. Some studies have demonstrated that MEST promotes invasion and metastasis of solid tumors and by coordinating and activating the NF-κB and Wnt/β-catenin signaling pathways (47,48), which is consistent with our findings of MEST gene and its related signaling pathways in ALL. The functional and clinical significance of MEST and its potential target against ALL 10.3389/fped.2022.999684 could be considered.…”
Section: Discussionsupporting
confidence: 92%
“…The tumor size and body weight were monitored every two days, and the tumor volume was calculated by the following equation: V = (length × width 2 )/2. At the end of the study, tumors were harvested for TUNEL assay, and several organs (liver, kidney, lung, and heart) were harvested for histologic analyses by Hematoxylin and Eosin (H&E) staining as previously described [ 22 ]. Briefly, the paraffin-embedded tissues fixed by paraformaldehyde were stained.…”
Section: Methodsmentioning
confidence: 99%
“…As a multifunctional protein, it participates in many cell biological processes, including protein degradation, membrane fusion, apoptosis, transcription activation and autophagy [9][10][11][12][13]. Studies have shown that VCP was over-expressed in many tumors and was associated with the occurrence, development and poor prognosis, including non-small cell lung cancer [14], colorectal cancer [15], prostate cancer [16], esophageal carcinomas [17], and breast cancer [18]. In previous studies, VCP was proved to be highly expressed and related to the metastasis of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%